PEMBERDAYAAN KELOMPOK WANITA TANI (KWT) BINA MANDIRI MELALUI PROGRAM KAWASAN RUMAH PANGAN LESTARI (KRPL) - Agustina Rusadi, Widya; Meilani, Yusi; Mubarok, Robby; Fitriyah, Sri; Triguna, Rizki; Dibyantoro, Dibyantoro (Berajah Journal, 2025)
Empowerment is an approach to enhance the capabilities or power of one party to the weaker or less powerful party. Kawasan Rumah Pangan Lestari (KRPL) is a program that utilizes environmentally friendly yards, aimed at fulfilling food and nutritional needs, as well as increasing income to improve community welfare. Juhut Village has implemented KRPL since 2014 and has the potential for further development. This study aims to analyze the empowerment of the Bina Mandiri Women Farmers Group (KWT) through KRPL. The method used is descriptive qualitative with purposive sampling in Juhut Village, Karangtanjung District, Pandeglang, Banten. The data used includes primary and secondary data, with a census method applied to 25 members of the KWT Bina Mandiri. Data collection techniques included observation, interviews, and literature studies. Data analysis was conducted descriptively and through tabulation. The results of the study indicate a significant impact on the increase in knowledge among KWT Bina Mandiri members regarding farming efforts, yard utilization, and fulfilling food needs through the KRPL program.